Managers' Cultural Background and Disclosure Attributes - Brochet, Francois; Miller, Gregory S.; Naranjo, Patricia; Yu, Gwen (The Accounting Review, 2019)
ABSTRACT We examine how managers' ethnic cultural background affects their communication with investors. Using earnings conference calls with executives from 42 countries, we find that managers from ethnic groups that have a more individualistic culture use a more optimistic tone and exhibit greater self-reference. Managers' ethnic culture has a lasting effect and persists for executives whose work experience later exposes them to different ethnic cultures. The effect of ethnic heritage is observed in dialogues that reflect real-time interactions (i.e., Q&A ) and is less pronounced in the scripted, less spontaneous portion of the calls (i.e., management discussion). Analysts respond positively to optimistic tone, but only those who share the manager's ethnic background adjust their earnings forecasts for the cultural component of managerial tone. The findings suggest that managers' ethnic background has a significant effect on how they communicate with the capital market and how the market responds to the disclosure.